Learn French with short stories : fifteen beginner stories with parallel French and English text - Hacking, French (Repro India, 2020)
French Hacking's "15 Short Stories" will allow you to progress your French and learn what and how to talk to sound like a native. Learning French doesn't have to be difficult. Most of what you learn in class and grammar books are rarely used in real life scenarios. Stop wasting your time and begin learning more efficiently.